Textbooks as Historical References in Teaching Geometry in Brazil Between 1925-2010 - Muccillo de Medeiros, Antonio Paulo; de Medeiros, Lícia Giesta Ferreira (Advances in Social Sciences Research Journal, 2021)
This paper makes a historical overview about how mathematics textbooks influenced geometry’s teaching in Brazil. Initially the study shows the relevance textbooks have as historical reference for a school discipline. Next, it describes how textbooks tend to transmit the same content in each historical period, a phenomenon Chervel called vulgata. From that point a timeline is created, since the first Brazilian mathematics textbook in 1744 until 2010, to understand how those volumes influenced geometry teaching. Four volumes, ranging from 1925 to 2010, are then analyzed. The focal point of this analysis is how triangles similarity is taught in each one of them. The paper also describes how government policies affected textbooks and school life in general since the beginning of mathematics teaching in Brazil.